Development of a novel multi‐strain wheat Qu with high enzyme activities for Huangjiu fermentation. (4th March 2021) - Yu, Peibin; Du, Jing; Cao, Chunlei; Cai, Guolin; Sun, Junyong; Wu, Dianhui; Lu, Jian
Abstract: BACKGROUND: Wheat Qu has long been used as a fermentation starter to produce Huangjiu. Wheat Qu quality depends on its microbial community structure and the hydrolytic enzymes generated by the micro‐organisms. RESULTS: Strain YF1 and YF2 were successfully screened as they exhibited high acidic protease (231.9 ± 1.4 U g −1 ) and cellulase (7.1 ± 0.6 U g −1 ) activities. Based on a morphological and sequence analysis of the internal transcribed spacer (ITS) gene, YF1 and YF2 were identified as Rhizopus oryzae and Aspergillus niger, respectively. Cooked wheat Qu was produced using mixed fungal starter fermentations with Aspergillus oryzae SU‐16, YF1, and YF2. For Qu‐making, the optimized conditions for fermentation time, water content, and inoculum size were 47.8 h, 69.4%, and 6.1%, respectively. Under these conditions, compared with single‐strain cooked wheat Qu, enzyme activities of amylase, acidic protease, and cellulase increased by 27.4%, 657.1%, and 1276.2%, respectively. Short peptides and free amino acids contents increased by 19.6% and 131.8%, respectively. This wheat Qu was used for Huangjiu brewing, and the alcohol content increased by approximately 14.6% because of the increased starch hydrolysis efficiency mainly attributed to its high enzyme activity. CONCLUSION: Using mixed fungal strains as starter cultures may be an efficient strategy to improve wheat Qu quality, with great potential for application in industrial Huangjiu production. © 2021 Society of Chemical Industry